Water at interfaces and its influence on the electrical properties of adsorbed films - Oliveira Jr., Osvaldo N.; Riul Jr., Antonio [UNESP]; Leite, Vitor Barbanti Pereira [UNESP] (Sociedade Brasileira de Física, 2004)
This paper discusses water at interfaces with emphasis on the electrical properties of adsorbed films. Two issues are addressed, namely adsorption of organic molecules at the air/water interface in Langmuir monolayers and the influence of adsorbed water on the electrical properties of nanostructured organic films deposited onto solid substrates. In Langmuir monolayers the focus will be on the interaction of the adsorbed molecules with the underlying water, particularly with regard to the surface potential and lateral conductance of the monolayers. It will be shown that these electrical measurements are extremely sensitive to small changes in the subphase, including trace amounts of impurities. Phase transitions due to structuring of the monolayer will be discussed at the light of theoretical models that deal with proton transfer along the monolayers. Attempts will be made to connect the interpretation at the molecular level with experimental findings from techniques such as Brewster angle microscopy and fluorescence microscopy, which provide information at the mesoscopic or microscopic scale. The gradient of the dielectric constant for water at the monolayer interface is inferred from modeling the monolayer surface potential in terms of the dipole moments of the molecules. For deposited films, the discussion will be centered on the electrical properties of nanostructured films produced with either the Langmuir-Blodgett (LB) or the layer-by-layer (LBL) methods. The strong effects from adsorbed water will be presented, with mention to sensor applications where the extreme sensitivity of the electrical properties to water is exploited and to doping of a conducting polymer induced by X-ray irradiation.